Impact Analysis of Oil and Gas Companies' CSR Programs for Mitigation and Adaptation of Climate Change Impact - Abdillah, Fahmi; Risqiani, Renny; Jakaria, Jakaria (International Journal Labs, 2023)
In the 6th assessment report published by the IPCC (Intergovernmental Panel on Climate Change), it is stated that the impact of climate change will be felt on the settlements and infrastructure of people living in coastal areas. The magnitude of this potential impact has encouraged the Anambas Islands Regional Government to include this impact in the Anambas Islands District Medium Term Development Plan for 2021-2026. Of course, synergy is needed in handling these impacts by involving all stakeholders, including oil and gas companies operating in this area. This study aims to determine the impact of climate change and the forms of community adaptation, as well as community perceptions of the contribution of oil and gas companies through the CSR change program in order to help mitigate climate impacts and also increase the adaptability of the community. Data was collected from all stakeholders as well as beneficiaries of the company's CSR program, by conducting in-depth interviews, observations, and also using a questionnaire. For the general public, climate change has begun to be felt with extreme weather conditions that often cause disasters, as well as decreased catches of fishermen in coastal areas. In fact, in certain seasons it will affect the smooth transportation of sea people, so that it can affect people's daily activities. Regarding the CSR program that has been carried out by oil and gas companies, the community considers this program very important for them, but further efforts still need to be made in order to meet their expectations, including increasing income.